Neutral and Charged Receptors as Voltammetric Sensors for Ions - Kaur, Karamjeet (My University, 2013)
Electrochemical studies for all the molecules were carried out using cyclic voltammetry. Neutral anthrone derivatives- anthrone1, anthrone2 and anthrone3 were studied electrochemically for sensing cations at galssy carbon electrodes. On the basis of the results obtained mechanism of metal ligand complexation on the electrode is proposed to explain the preferential oxidation at the electrode. Anthrone derivatives showed selectivity toward copper and mercury ions even in the presence of other metal ions. Electrochemical reaction of anthrone3 was identified as a kinetically controlled process rather than a diffusion-controlled process based on different scan rates. Influence of polarity of the solvent on the shape and peak position is also studied. Electrochemical behavior of positively charged anthrone derivatives BPODS and BPMS, functionalized with viologen group were inspected extensively using cyclic voltammetry, taking clue from colorimetric studies of these molecules indicating their selectivity towards anions like cyanide, acetate and fluoride. Cation selectivity of anthrone derivative changed to anions because of the viologen group. Anthrone derivative stabilizes viologen through conjugation, reducing one of its two redox couples which are characteristics of viologen group for molecule 1. Mechanisms were proposed duly supported by density functional theory calculation based theoretical studies carried out using Guassian 03W for the electrochemical behaviour of the compounds 1 and 2. Voltammograms of dicationic viologen derivative 1 showed near quenching of anodic peaks (a decrease of almost 90% of current) as well as cathodic peaks (a decrease of almost 100% current) in presence of 1 equivalent of cyanide ions. The monocationic viologen derivative 2 also showed quenching of the cathodic peak while anodic peak survives in presence of the anions, cyanide, acetate and fluoride. The proposed electrochemical sensors were selective for CN-, OAc- and F- based on binding constants which are much larger than for anions like Cl-, Br-, I-, HSO4 - and have also been used for determination of unknown samples of cyanide ions. Neutral imidazole based molecules TPAN, TPF, TPIM and TPIAM showed irreversible electrochemical nature as only oxidation peaks were obtained. All the four molecules as a sensor gave selective and distinguishable signals on interaction with Cu2+ and Hg2+ ions xviii with no interference from other potentially interfering ions like Zn2+, Pb2+, Co2+, Ni2+. Differential pulse voltammetry studies of TPAN and TPF with metal ions showed that both the molecules interact differently with Hg2+ and Cu2+ ion. Two types of electrode modifications were done: one anthrone3 modified screen printed electrode and second is polyaniline modified glassy carbon electrode with ionophore (TPAN and TPF) drop coated on the surface. The voltammetric study of anthrone3 conducted in 1:1 water-acetonitrile solvent system was compared with modified screen printed electrode (SPE-A) and anthrone3 in solution phase. Anthrone3 displayed an electrochemically quasi-reversible nature in voltammograms with both the systems and is presented as a novel disposable voltammetric sensor for mercury ions. Upon interaction with cations, both the electrode systems showed sensitivity towards Hg2+ ions with a lower detection limit of 0.61M. The magnitude of the voltammetric current with the SPE-A exhibited three times the current obtained with a bare glassy carbon electrode (GC). Polyaniline modified gave better results than unmodified GC electrode. As tested with ferrocene it was found to be highly permeable. Results obtained after modifying the electrode with ionophores TPAN and TPF were better than bare GC electrode results in terms of peak current intensity. On the basis of selectivity shown by TPAN and TPF toward ions Hg2+ and Cu2+ ions, ionophore/PANI/GC modified electrode was also used to sense these ions and for their determination in soil sample of CFL dump site.
Doctor of Philosophy-Thesis
Keywords: Cyclic voltammetry; anthione; imidazole; DVP